2019
DOI: 10.1007/s10509-019-3511-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dark matter in star formation

Abstract: The standard model for the formation of structure assumes that there existed small fluctuations in the early universe that grew due to gravitational instability. The origins of these fluctuations are as yet unclear. In this work we propose the role of dark matter in providing the seed for star formation in the early universe. Very recent observations also support the role of dark matter in the formation of these first stars. With this we set observable constraints on luminosities, temperatures, and lifetimes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Ongoing studies have been focusing on different aspects of compact objects, including bosonic DM stars (Eby et al 2016;Lee et al 2021, in preparation), formation of neutron stars through the accretioninduced collapse of DM-admixed white dwarfs (WDs; Leung et al 2019;Zha et al 2019), tidal properties of DM-admixed neutron stars (Leung et al 2021, in preparation), thermalization of the WD core to produce a thermonuclear runaway (Bramante 2015;Acevedo & Bramante 2019;Janish et al 2019;Steigerwald et al 2019), and thermonuclear supernovae with point-mass DM cores (Leung et al 2015a). Other than compact objects, effects of DM admixture on stellar formation (Arun et al 2019) and evolution (Scott et al 2008;Freese et al 2016;Lopes & Lopes 2019) are actively investigated. In particular, the evolution of AGB stars is used to constrain the properties of axion-like particles (Dolan et al 2021).…”
Section: Dm-admixed Stellar Objectsmentioning
confidence: 99%
“…Ongoing studies have been focusing on different aspects of compact objects, including bosonic DM stars (Eby et al 2016;Lee et al 2021, in preparation), formation of neutron stars through the accretioninduced collapse of DM-admixed white dwarfs (WDs; Leung et al 2019;Zha et al 2019), tidal properties of DM-admixed neutron stars (Leung et al 2021, in preparation), thermalization of the WD core to produce a thermonuclear runaway (Bramante 2015;Acevedo & Bramante 2019;Janish et al 2019;Steigerwald et al 2019), and thermonuclear supernovae with point-mass DM cores (Leung et al 2015a). Other than compact objects, effects of DM admixture on stellar formation (Arun et al 2019) and evolution (Scott et al 2008;Freese et al 2016;Lopes & Lopes 2019) are actively investigated. In particular, the evolution of AGB stars is used to constrain the properties of axion-like particles (Dolan et al 2021).…”
Section: Dm-admixed Stellar Objectsmentioning
confidence: 99%
“…On-going studies focus on different perspectives of compact stars including bosonic DM stars (Eby et al 2016), formation of a neutron star through accretion-induced collapse of a DM-admixed white dwarf (Leung et al 2019;Zha et al 2019), thermalization of the white dwarf (WD) core to produce thermonuclear runaway (Bramante 2015;Acevedo & Bramante 2019;Janish et al 2019;Steigerwald et al 2019), and point-mass DM-admixed in thermonuclear supernovae (Leung et al 2015a). Recent studies have been made on DM-admixed pulsars (Rahman et al 2020), effects of DM admixture on star formation (Arun et al 2019), bosonic DM-admixed neutron stars with relativistic Bose-Einstein Condensation (Lee et al, in prep) and tidal Love numbers of DM-admixed neutron stars (Leung et al, in prep). DM-admixed astrophysical objects have become a new window to search for astrophysical DM.…”
Section: Dm Admixed Stellar Objectsmentioning
confidence: 99%
“…Besides terrestrial experiments, physicists are tackling the DM problem through astrophysical observations. It is shown that in a region with a high concentration of DM particles, DM could be captured by normal matter (NM, Sulistiyowati et al 2014;Arun et al 2019). Therefore, it is natural to expect stellar objects composed of NM and DM.…”
Section: Introduction 1dark Matter-admixed Astrophysical Objectsmentioning
confidence: 99%